Book review: Amiya P. Sen, An Idealist in India: Selected Writings and Speeches of Sister Nivedita. (December 2020) - Arya, Geeta
Amiya P. Sen, An Idealist in India: Selected Writings and Speeches of Sister Nivedita . New Delhi: Primus Books, 2016, xi + 225 pp., ₹1450, ISBN: 9789384082932.